Access and utilization of financial services among poor HIV-impacted children and families in Uganda. (February 2020) - Sun, Sicong; Nabunya, Proscovia; Byansi, William; Sensoy Bahar, Ozge; Damulira, Christopher; Neilands, Torsten B.; Guo, Shenyang; Namuwonge, Flavia; Ssewamala, Fred M.
Highlights: We examine determinants of saving performance among HIV-impacted children. Poor HIV-impacted families can save if institutional arrangements are in place. Compared to individual factors, institutional factors play a more pronounced role. Findings have implications for financial inclusion policy and programming. Abstract: With high prevalence of both poverty and HIV, Sub-Saharan Africa (SSA) has one of the highest numbers of unbanked individuals and families. Although the use of savings products to promote financial inclusion among poor individuals and families has increasingly become more important to policy makers in SSA, limited research exists about the mechanisms and relative importance of institutional and individual-level factors associated with access and utilization of financial services. Using survey data and administrative bank records from a randomized controlled trial in southwestern Uganda, we find that given an opportunity, poor HIV-impacted families and individuals can engage with financial institutions and accumulate savings. Additionally, individual-level factors (e.g., household wealth, child poverty, child work, and attitudes towards savings) were significantly associated with three of the eight outcomes (i.e. saved any money, average monthly total savings, and total number of deposits). Furthermore, institutional-level factors (e.g., access and proximity to the bank, matching incentive rate, and financial education) were associated with all the eight outcomes included in the analysis. Our findings indicate that poor HIV-impacted families can engage with financial institutions and save for their children, if opportunities and institutional arrangements are in place. Findings have implications for financial inclusion policy and programming that target vulnerable youth and families to engage with financial institutions and accumulate savings.